Taxonomic Account of the Indian Populus L. (Salicaceae Mirb.) With Special Emphasis on their Distribution and Identification - Chanda, Sukla; Pramanik, A.; Maiti, G. G. (Indian Forester, 2011)
The genus Populus L., belongs to the family Salicaceae Mirb. having 35 species of worldwide distribution. In India, total 8 taxa are known mainly distributed throughout the Himalayas. Species like P. alba L., P. balsamifera L., P. deltoides Bartram ex Marshall, P. euphratica Olivo and P. nigra L. var. italica Du Roi are confined to the north-western parts of India while P. gamblei Dode and P. glauca Haines are found in the north-eastern parts. P. ciliata Wall. ex Royle is the most common species found both in the eastern as well as western Himalayas. Nature of the axillary buds and the terminal buds, number of valves in the capsules are the useful characters for identification of these species but one of the most important feature is the leaf character through which one can easily identify the species in the field as well as while the species are in non-floriferous condition. The distribution pattern with two maps of these 8 species is discussed. An artificial key is provided along with illustrations of leaf characters for easy identity.